2001
DOI: 10.1002/jcb.1212
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the biologically important interaction between troponin C and the N‐terminal region of troponin I

Abstract: The N-terminal regulatory region of Troponin I, residues 1-40 (TnI 1-40, regulatory peptide) has been shown to have a biologically important function in the interactions of troponin I and troponin C. Truncated analogs corresponding to shorter versions of the N-terminal region (1-30, 1-28, 1-26) were synthesized by solid-phase methodology. Our results indicate that residues 1-30 of TnI comprises the minimum sequence to retain full biological activity as measured in the acto-S1-TM ATPase assay. Binding of the Tn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 63 publications
(39 reference statements)
2
16
0
Order By: Relevance
“…A number of other studies have also concluded that TnIp interacts primarily with regions in the C-terminal domain (Lan et al, 1989;Wang et al, 1990;Ngai & Hodges, 1992;Swenson & Frederickson, 1992;Ngai et al, 1994). Fluorescent probes reveal that, although intact sTnI is bound to both the N-and C-terminal domains of sTnC, the inhibitory fragments of sTnI (96-1 16 and 104-1 15) interact mainly with the C-terminal domain connecting strand of sTnC (Lan et al, 1989).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A number of other studies have also concluded that TnIp interacts primarily with regions in the C-terminal domain (Lan et al, 1989;Wang et al, 1990;Ngai & Hodges, 1992;Swenson & Frederickson, 1992;Ngai et al, 1994). Fluorescent probes reveal that, although intact sTnI is bound to both the N-and C-terminal domains of sTnC, the inhibitory fragments of sTnI (96-1 16 and 104-1 15) interact mainly with the C-terminal domain connecting strand of sTnC (Lan et al, 1989).…”
Section: Discussionmentioning
confidence: 96%
“…Numerous studies have suggested that sTnIp interacts with both the N-and C-terminal domains of sTnC (Kobayashi et al, 1991;Ngai & Hodges, 1992;Swenson & Frederickson, 1992;Farah et al, 1994). An explanation for these observations is that TnC, like CaM, folds over the peptide such that both domains make contact with the inhibitory peptide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their data provided evidence in support of a significant function of a cTnT-binding domain in cTnI, and they suggested that cTnT binding to the N-terminus of cTnI is a negative regulator of cardiac activation. More recently, Ngai et al have characterized a minimum sequence of the N-terminus of TnI (residues 1-30) that retains full biological activity to bind the C-terminal domain of TnC [49], and showed that the N-and C-terminal domains of TnI act as a Ca 2+ -dependent switch for TnC [50]. Thus, the N-terminal region of TnI may participate in the calcium activation of muscle contraction in cardiac and skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Based on several experimental approaches, such as crystallography [1][2][3], NMR [4][5][6], neutron scattering [7,8], chemical crosslinking [9-11] and fluorescence resonance energy transfer [12,13], a structural model of the TnC-TnI complex was proposed in which TnI winds around TnC in either a lefthanded manner (Model ÔLÕ) or a right-handed manner (Model ÔRÕ) [14]. According to these models, five adjoining segments of TnI, segment I-V, correspond to residues 3-33, [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114] respectively. Segment…”
mentioning
confidence: 99%